ASSESSMENT OF READINESS OF GONDOKUSUMAN SUB-DISTRICT IN FILLING INTEGRATED PALLIATIVE CARE FOR OLDER PEOPLE - Wilianto, Maria G; Perdamaian, Teguh K; Sigilipoe, Mitra A; Widagdo, M M (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background : Every year the number of elderly people in Indonesia continues to increase. In 2018 the highest number of elderly people was in the DI Yogyakarta Province, amounting to 12.37%. Data from Riskesdas showed that 51.28% of the elderly experienced health complaints and 25.99% of the elderly experienced illness. This can reduce the patient's quality of life. Therefore, integrated palliative care is needed for the elderly to improve the quality of life for patients and their families in dealing with health problems. Palliative care already exists in 5 hospitals in 5 regions in Indonesia, namely DKI Jakarta, DI Yogyakarta, Surabaya, Denpasar, and Makassar.Objective : The general objective of this study was to explore the readiness of Gondokusuman District in fulfilling integrated palliative care for the elderly.Method : This study used a thematic analysis research design. The research sample was 46 respondents. The data is taken from previous research entitled